Sharps Accidents: Occurrence and Knowledge Level among Brazilian Dental Students - Alice Marques Vidal Freitas; Amanda Leal Meireles; Millena Barroso Oliveira; Marcelo Bighetti Toniollo; Lázara Joyce Oliveira Martins; Cláudio Rodrigues Rezende Costa; Andrea Sayuri Silveira Dias Terada (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate the prevalence of sharps accidents among dental students in southwest Goiás state, Brazil, and further survey their knowledge of biosafety and post-injury management. Material and Methods: A cross-sectional analytical observational study was carried out in 2018 following the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. The study population included dental students in the 4th and 10th course semester. A pre-formulated self-administered questionnaire containing 14 objective questions was used for data collection. Mean and standard deviation values were calculated. Results: A total of 308 responses were obtained. Overall, 15.9% of the respondents reported having previously experienced accidents with sharps. Most dental students who claimed to know the biological risks to which they are exposed were in the 5th and 8th course semesters, and 67.2% of them reported knowing how to proceed in the event of a sharp accident. Conclusion: A low prevalence of sharps accidents has been reported, and dental students are considered to have a good knowledge of biosafety.